Experimental Study of The Influences of Inclination Angle and Heat Load on Loop Heat Pipe Thermal Performance - Pramesywari, Afifa; Kusuma, Mukhsinun Hadi; Kiono, Berkah Fajar Tamtomo; Rozi, Khoiri; Giarno, Giarno; Pambudi, Yoyok Dwi Setyo; Hatmoko, Sumantri; Emara, Haura (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2024)
The utilization of nuclear power brings out a lot of benefits in fulfilling human power needs, however, the thermal incident caused by the failure of an active cooling system because of an earthquake followed by the tsunami such as on the Nuclear Power Plant at Fukushima Dai-Ichi Japan could be taken for lesson learn to keep improve nuclear installation operation safety aspects. Loop heat pipe (LHP) as an alternative cooling system technology could be utilized to handle thermal problems on nuclear installations. This research aims to know the influence of the inclination angle and heat load on the LHP thermal performance. The experimental investigation was performed with varying the inclination angle of 0°, 2.5°, and 5°, and heat load given at 60°C, 70°C, 80°C, and 90°C. LHP was used demineralized water working fluid with a 100% filling ratio. LHP was vacuumed on 2.666,4 Pa. The cooling air velocity in the condenser given by 2,5 m/s. The result of this experiment showed that LHP has the best thermal performance with the lowest thermal resistance of 0.0043°C/W. This result was obtained when the LHP operated with a 5° inclination angle and hot water as the heat load of 90°C. The conclusion from this research is showing better LHP thermal performance as the inclination angle increase on LHP because the steam speed that formed bigger, and condensate flows back to the evaporator faster